PENGARUH TINGKAT INFLASI, SUKU BUNGA BI, DAN NILAI TUKAR RUPIAH TERHADAP IHSG - Desi Ratjaya Ningsih; Nur Aida Arifah Tara; Muhdin Muhdin (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
The Composite Stock Price Index (IHSG) is a description of information regarding the movements of all stock prices that affect capital market conditions and produce a trend. There are three factors that mainly influence the IHSG, namely inflation, BI interest rates, and the rupiah exchange rate. The purpose of this study was to examine the relationship between inflation, BI interest rates, rupiah exchange rate and the IHSG in the period of 2016-2020. The method in this research used quantitative methods. The results showed that inflation and BI interest rates have a negative and insignificant effect on the IHSG, while the Rupiah exchange rate has a significant negative effect on the IHSG.Keywords :IHSG, Inflasi, Suku Bunga BI, Nilai Tukar Rupiah